Probiotics and conventional terapy: new fronter in therapeutic approach in articular manifestations of IBD - Tomasello, Giovanni; Palumbo, Vincenzo Davide; Miceli, Angelo; Sinagra, Emanuele; Bruno, Antonio; Abruzzo, Alida; Cappello, Francesco; Patti, Angelo Maria; Giglio, Rosaria Maria; Damiani, Provvidenza; Tomasello, Riccardo; Noto, Marcello; et al. (Progress in Nutrition, 2014)
This work reports a clinical trial performed at Palermo University Hospital “Paolo Giaccone”. From January 2004 to December 2011, 79 patients were enrolled (40 men and 39 women). All patients suffered from Inflammatory Bowel Disease (IBD) and were subjected to orthopedic consultation at the Institute of Orthopaedics, University Hospital of Palermo, for arthropathy secondary to IBD. The patients were divided into two groups (A and B) and dealt with different therapies for the resolution of the inflammatory picture of the colonic mucosa and the treatment of the extraintestinal articular manifestations. Group A was treated with drug therapy: Diclofenac (75 mg im/day for 10 days) and Mesalazine (800 mg gastro-resistant tablets, one tablet twice a day in mild forms, and one tablet three times per day in moderate forms). In group B, in addition to the previous treatment protocol, two probiotic mixtures were added in a time of two weeks: in the first week, twice a day, one capsule containing a mixture of Enterococcus faecium and Saccharomyces boluard was administered, with the main purpose to mitigate the intestinal inflammation; in the second week, twice a day too, one capsule containing a mixture of Lactobacillus salivarius and Lactobacillus acidophilus was administered, with the aim to promote the restoration of a normal intestinal microenvironment. The attenuation of intestinal inflammation, improved by the presence of probiotics, could have important effects on the articular manifestations, resulting in a significant improvement of the arthropathy. All patients were evaluated with the Harvey-Bradshaw Index. Both Crohn Disease and Ulcerative Cholitis diagnosis was made with clinical, laboratory, endoscopic and instrumental tests; the degree of disease activity was evaluated using the criteria of Truelove and Witts. The WOMAC-Score (Western Ontario McMaster) was used in our study to investigate the degree of articular involvement of the patients. The data were statistically evaluated and these are shown that the B group of patients treated with conventional therapy + probiotic mixture had a better resolution of the clinical and of this post-treatment parameters: WOMAC score, ESR, CRP and white blood cells; and also the B group of patients have a better response to standard therapy compared with patients who did not receive the probiotic with a remarkable statistic significance (p≤0.0001).